Spatio-Temporal Nonlinear Modeling of Gastric Myoelectrical Activity - Wang, Z. S.; Cheung, J. Y.; Gao, S. K.; Chen, J. D. Z. (Methods of Information in Medicine, 2000)
The accomplishment of a complete digestive process of human stomach is regulated by a spatio-temporally-coordinated electric pattern called gastric myoelectrical activity (GMA). The normal patterns of GMA present temporal evolution from endogenous rhythmic oscillation to bursting of spikes associated with contractions, and also ordered spatial propagation of the oscillating waves. The abnormal patterns of GMA have been observed in temporal dysrhythmia, such as tachygastria, bradygastria and arrhythmia, and in spatial propagation failure, such as retrograde propagation and uncoupling. Different GMA patterns are associated with different gastric symptoms and there exist some nonlinear mechanisms to govern the formation and dynamic evolution of these patterns. However, these mechanisms are so complex that few of them are known by medical observations. The aim of this study is to explore these mechanisms by spatio-temporal modeling of GMA. The single-cell model simulating the formation process of slow waves and spikes, the multi-cell model simulating the propagation process of GMA and the extracellular model simulating the formation of bipolar recordings are presented.
Keywords: Spatio-temporal Nonlinear Modeling; Gastric Myoelectrical Activity; Chaos